Asynchronous Distributed Algorithms for Heading Consensus of Multi-Agent Systems with Communication Delay - Li, Qin; Jiang, Zhong-Ping (Asian journal of control, 2013)
In this paper, we propose two asynchronous distributed protocols for the heading consensus of a multi‐agent group which cannot access a global coordinate system and a global time. Both the leaderless and leader‐following cases are addressed, and inter‐agent communication delay is taken into account. It is proved, under some standard connectivity assumptions, that our leaderless algorithm ensures the heading consensus provided the initial headings are not balanced; and the leader‐based algorithm guarantees the global heading consensus.